A proof‐of‐concept study of the removal of early and late phase biofilm from skin wound models using a liquid acoustic stream. Issue 8 (26th April 2022) - Secker, Thomas J.; Harling, Christopher C.; Hand, Chloe; Voegeli, David; Keevil, Charles W.; Leighton, Timothy G.
Abstract: Chronic wounds fail to progress through the normal stages of healing, with the largest remediable cause of chronicity being presence of a multi‐species biofilm. Removal of biofilm from the wound environment is central to wound care. A device for mechanically removing biofilms from wounds has been devised. The removal is caused by small‐scale liquid currents and shear, generated by acoustically activated microscopic air bubbles. These bubbles and acoustic waves are delivered onto the wound by a gentle liquid stream, allowing cleaning in situ and removal of debris in the run‐off liquid. We have investigated if this liquid acoustic wound stream (LAWS) can remove bacterial biofilm from soft biological wound models and studied the effect of LAWS on the cellular tissues of the substrate. LAWS will efficiently remove early Pseudomonas aeruginosa biofilm from an artificial wound in a pig's trotter, 24 hours‐mature biofilm of P. aeruginosa from a pre‐wounded human full thickness skin model (EpiDerm FT), and 3‐day mature biofilm of P. aeruginosa or Staphylococcus aureus from a porcine skin explant. Histological examinations of uninfected EpiDerm models that had been treated by LAWS and then stained with Haematoxylin and Eosin, demonstrated no damage to the human tissue, and wound diameter was smaller in the treated skin models compared with untreated samples. Immunofluorescence staining for cytokeratin 14 showed that keratinocytes had migrated further across the wound in the uninfected samples treated by LAWS. We discuss the implications for wound healing and propose further laboratory and clinical studies to demonstrate the removal of biofilm from patients with chronic leg ulcers and the impact on healing.